Fra-2/AP-1 regulates melanoma cell metastasis by downregulating Fam212b - Chen, Guang Liang; Li, Rui; Chen, Xiao Xiang; Wang, Juan; Cao, Shan; Song, Rui; Zhao, Ming Chun; Li, Li Ming; Hannemann, Nicole; Schett, Georg; Qian, Cheng; Bozec, Aline (Cell Death and Differentiation, 2020)
Metastatic melanoma remains a challenging disease. Understanding the molecular mechanisms how melanoma becomes metastatic is therefore of interest. Herein we show that downregulation of the AP-1 transcription factor member Fra-2 in melanoma cells is associated with an aggressive melanoma phenotype in vitro and in vivo. In vitro, Fra-2 knockdown in melanoma cells promoted cell migration and invasion associated with increased Snail-1, Twist-1/2, and matrix metalloproteinase-2 (MMP-2) expression. In vivo, Fra-2 knockdown in a melanoma cell line led to increased metastasis into the lungs and liver. The increased metastatic potential of Fra-2 knockdown melanoma cells was likely due to an accelerated cell cycle transition and increased tissue angiogenesis. Using Fra-2 knockdown cell lines microarray analysis, we identified the protein Fam212b (family with sequence similarity 212 member B) as a downstream target of Fra-2. By additional knockdown of Fam212b in Fra-2 mutant cells, we mitigated the cell migration, invasion, and cell cycle transition phenotype induced by Fra-2 knockdown. Furthermore, Fam212b overexpression enhanced β-catenin pathway. Finally, Fam212b expression is correlated with increased melanoma metastasis and poor clinical outcomes in human patients. In summary, these findings reveal the Fra-2-Fam212b axis as a new pathway of melanoma metastasis, which can be in the future used as potential marker of the metastatic properties of melanoma.
CRIS-Team Scopus Importer:2020-11-20